Pollination and dispersal systems in a Cerrado remnant (Brazilian Savanna) in Southeastern Brazil - Ishara, Katia Losano [UNESP] (2011)
The aim of this work was to identify the pollination and dispersal systems among the species in a disjunct marginal cerrado area and to compare the frequency of these systems to those found in other Neotropical vegetation. The floral and diaspore traits and the pollination and dispersal systems of 176 species were analysed in a cerrado remnant in Southeastern Brazil. The most frequent pollination system was melittophily (63% of the studied species) with the remaining 37% distributed among diverse pollination systems. Zoochory was the predominant system of dispersal (44.9%). The frequencies of melittophily and zoochory observed in diverse tropical areas were the main feature that allowed the formation of distinct groups in the dendrograms generated by cluster analysis.